Toward a Change Among the Epidemiology of Catheter-Related Bloodstream Infections in Catalonia. (October 2020) - Gasch, Oriol; Andrés, Marta; Camara, Jordi; Llobregat, L'Hospitalet de; Domenech, Dolors; Jimenez, Emili; Llobregat, L'Hospitalet de; Marrón, Anna; Meije, Yolanda; Pomar, Virginia; Saliba, Patrick; Calbo, Esther
Abstract : Background: Catheter-related bloodstream infections (CRBSIs) are one of the most frequent causes of heathcare-associated infections and an important cause of preventable death. Central venous catheters (CVC) have been considered the most worrisome origin of CRBSI. Implemented preventive measures at most hospitals and published guidelines for the prevention of vascular catheter infections have focused mostly on CVCs. However, peripherally inserted venous catheters (PIVC)–related bloodstream infections have increased in recent years and are currently among the top 10 patient safety concerns for 2019. Objective: We describe the changes in the epidemiology of catheter-related bloodstream infections among acute-care hospitals reporting at the VINCat program (Infection Control and Antimicrobial Stewardship Catalan Program) from 2008 to 2018. Methods: Data on 55 hospitals in Catalonia reporting all the episodes of CRBSI diagnosed according to standardized definitions during 2008–2018 were used for the analysis. Participating hospitals were classified into 3 groups according to size: group 1 (>500 beds), 9 hospitals; group 2 (500–200 beds), 17 hospitals; and group 3 (<200 beds), 29 hospitals. Catheters were classified in 3 categories: CVCs, PICVCs, and short peripheral venous catheters (PVCs). Rates of catheter-related bloodstream infection (CR-BSI) were obtained by adjusting the total number of episodes by 1, 000 hospital stays. Simple linear regressions were performed. Values of P ≤ .05 were considered statistically significant. Results: During the study period, 8, 221 nosocomial episodes of CRBSI were diagnosed among the 55 participating hospitals. In total, 37, 587, 967 hospital stays were counted. The CRBSI rate was 0.22 episodes per 1, 000 hospital stays (group 1, 0.28; group 2, 0.15; and group 3, 0.16), following a downward trend from 2008 to 2018 from 0.28 to 0.21 per 1, 000 hospital stays ( P < .005). Among them, CVC-BSI showed a downward trend (from 610 annual episodes in 2008 to 312 in 2018), and PICVC and PVC showed an upward trend (from 51 and 120 annual episodes in 2008 to 130 and 312 in 2018, respectively). Annual rates of PICVCs and PVCs showed an upward trend, but CVCs showed a downward trend in 2018 ( P < .05): 0.09 per 1, 000 hospital stays for PICVCs; 0.07 per 1, 000 hospital stays for PVCs, and 0.04 episodes per 1, 000 hospital stays for CVCs (Fig. 1). Conclusions: PIVC-related bloodstream infections have increased in recent years, whereas bloodstream infections related to CVC have followed a downward trend. Our hospitals should implement preventive measures to specially address the prevention of PICVC infections. Funding: None Disclosures: None